Socialization to increase conservation initiative for the younger generation in Tahura Bukit Mangkol, Central Bangka - Nurzaidah Putri Dalimunthe; Ilpandari Ilpandari; Hendi Hendra Bayu; Rahmad Lingga (Community Empowerment, 2022)
The community's active involvement in resolving issues and challenges in the field determines the effectiveness of the conservation initiative. A socialization program with the focus on wildlife conservation is required to enhance awareness and conservation efforts for the neighborhood surrounding the Bukit Mangkol Forest Park. The objective of this community service is to raise the younger generation's understanding and awareness of environmental preservation, particularly with regard to the typical Bangka Belitung wildlife found in the Bukit Mangkol Forest Park. Socializing and discussing are the methods of community service. The socialization's outcomes demonstrated that there was an improvement in participant understanding of wildlife threats, wildlife conservation strategies, and actual action taken by participants to protect nature for sustainable development.